Effect of Substrate Material on the Electromagnetic Properties of the Photolithography Printed Antenna - Thiyaneswaran Balashanmugam; Aruna Devi Baladhandapani; Palanivel Rajan Selvakumaran; Dhanagopal Ramachandran; Suresh Kumar Muthuvel; Priyadharshini Sivaraj; Samson Alemayehu Mamo (Advances in Materials Science and Engineering)
In this study, a rectangular microstrip feed antenna on a fire-retarded substrate is presented. The antenna is designed using Computer Simulation Tool (CST) software. Different materials are used for the substrate, and the electromagnetic properties of the proposed structure are analyzed for each material. The EM property variation for each material is comparatively presented. The proposed antenna has CSRR (Complementary Split-Ring Resonator) which is engraved on the radiating element, and the shape of the CSRR is the hexagon. The proposed metamaterial-inspired antenna exhibits multiband operation at 2.1 GHz, 2.6 GHz, 4.6 GHz, 5.5 GHz, 6.1 GHz, and 7.1 GHz. With the help of material analysis, the fire-retarded substrate is chosen for the design, its excellent EM properties, and cheap cost. The photolithography-based printed antenna is validated with the help of S11, VSWR, gain, directivity, surface current distribution, and radiation pattern. Simple, compact structure, good gain, stable radiation pattern, and excellent EM properties of the fire-retarded substrates make it suitable for the GHz application.